Temat: Rozwiązywanie zadań pierwszego stopnia z jedną niewiadomą.
a) 5-2(2-z)=3
b) 7(3y+1)-6(2y+3)=-2
c) 4(1,2x-0,75)+5(3-1,2x)=3
d) 4(x+3)-5=7
e) -10-(x-2)=14+x
f) 4-x=2x+5
g) 7y+3=9y+13
h) (2x+3)-(2x+3)=-3
i) 1-2y=5y-1
j) 2m+1=4m(2-1)+4

2

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T18:22:13+01:00
A) 5-2(2-z)=3
5-4+2z=3
2z=3-5+4
2z=2
z=1
b) 7(3y+1)-6(2y+3)=-2
21y+7-12y-18=-2
9y=-2-7+18
9y=9
y=1
c) 4(1,2x-0,75)+5(3-1,2x)=3
4,8x-3+15-6x=3
-1,2x=-9
x=7,5
d) 4(x+3)-5=7
4x+12-5=7
4x=7-12+5
4x=0
x=0
e) -10-(x-2)=14+x
-10-x+2=14+x
-x-x=14+10-2
-2x=22
2x=-22
x=-11
f) 4-x=2x+5
-x-2x=5-4
-3x=1
x=-1/3
g) 7y+3=9y+13
7y-9y=13-3
-2y=10
2y=-10
y=-5
h) (2x+3)-(2x+3)=-3
2x-3-2x-3=-3
0=3 równanie sprzeczne, brak rozwiązania
i) 1-2y=5y-1
-2y-5y=-1-1
-7y=-2
y=2/7
j) 2m+1=4m(2-1)+4
2m+1=4m+4
2m-4m=4-1
-2m=3
2m=-3
m=-3/2
2010-03-09T18:25:55+01:00
A) 5-2(2-z)=3
5-4+2z=3
2z=2
z=1
b) 7(3y+1)-6(2y+3)=-2
21y+7-12y-18=-2
9y=9
y=1
c) 4(1,2x-0,75)+5(3-1,2x)=3
4,8x-3+15-6x=3
4,8x-6x=3+3-15
-1,2x=-6
x=5
d) 4(x+3)-5=7
4x+12-5=7
4x=0
x=0
e) -10-(x-2)=14+x
-10-x+2=14+x
-x-x=14-2+10
-2x=22
x=-11
f) 4-x=2x+5
-3x=1
x=-⅓
g) 7y+3=9y+13
-2y=10
y=-5
h) (2x+3)-(2x+3)=-3
2x+3-2x-3=-3
0x=-3
i) 1-2y=5y-1
-7y=-2
y=dwie siódme
j) 2m+1=4m(2-1)+4
2m+1=8m-4m+4
-2m=3
m=-1,5


licze na naj ;]